Comparison of two Wireless Electromyography Sensor Module Designs using wet electrodes and dry electrodes at the time of Sitting motion to stand - Farid Amrinsani; Levana Forra Wakidi; Made Dwi Pandya Suryanta; Dessy Tri Wulandari; Wahyu Caesarendra (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
One of the biosignals used to identify muscle signals in humans is electromyography. Electromyography signals are frequently utilized as input and are designed to aid in post-stroke therapy recovery or to assist people with disabilities. This phenomena has led to the development of numerous electromyography module sensor designs for use in support of various research-based applications. In this study, an electromyography sensor module without an electrode cable is compared to an electromyography sensor module that uses gel electrodes, plate electrodes, electrode cables, and other electrode technologies. A function generator is used to test each module, and the correlation value is sought to determine the connection between the two modules under consideration. Later, the findings of this study served as the foundation for other studies. Researchers also wish to explore the possibility of developing an electromyography sensor module by altering the wireless EMG sensor module's structure and design. Whereas this study can subsequently be extremely helpful to improve the standing of the Health Poltekkes Kemenkes Surabaya.